2020
DOI: 10.3390/su12208655
|View full text |Cite
|
Sign up to set email alerts
|

How Does Improve Farmers’ Attitudes toward Ecosystem Services to Support Sustainable Development of Agriculture? Based on Environmental Kuznets Curve Theory

Abstract: Agroecosystems are complex socio-ecological systems that are managed by farmers to achieve desired outcomes, including economic income and environmental benefits contributed by ecosystem services (ES). Therefore, understanding farmers’ attitudes for ES will provide references for targeted agricultural environment management, which is critical to achieving the sustainable development of agriculture. The aim of this study is to identify the attitudes of farmers regarding ES, and to test whether and how annual ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 76 publications
(111 reference statements)
0
7
0
Order By: Relevance
“…This study analyses the nonlinear relationship between agricultural ESs and annual household income. The EKC hypothesis of agricultural ESs assumes that it talks about a U-shaped curve to focus on the problem of under-provision of a positive externality [ 28 , 48 ]. The results do not support a U-shaped hypothesis of EKC for agricultural ESs ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study analyses the nonlinear relationship between agricultural ESs and annual household income. The EKC hypothesis of agricultural ESs assumes that it talks about a U-shaped curve to focus on the problem of under-provision of a positive externality [ 28 , 48 ]. The results do not support a U-shaped hypothesis of EKC for agricultural ESs ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Actually, these single-variable indicators of environment degradation are a multifaceted problem and have some definite relations with different stages of economic development, which can be explained in one such EKC relation [ 14 , 25 ]. From the circumstance about agrarian economies exploiting more natural resources and ESs, the analysis of environment-economy about agroecosystem should be valuable to further consider the problem of under-provision of a positive externality (ecosystem services), rather than the problem of the over-supply of a negative externality (pollution) [ [26] , [27] , [28] ]. In addition, the integrative environmental index based on the ESs can be used within research on sustainable development to detect the problem of under-provision of a positive externality in agroecological environment [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Niğde Province is known for apple production in Türkiye (Bozbuğa and Pırlak, 2012) while poplar, oak, black pine, hawthorn and weeping willow are well adapted trees growing commonly in Central Anatolia (Çalişkan and Boydak, 2017;Ertug, 2000) and these are common trees in Niğde Province. Tree knowledge is important to guiding the farmer choice and preference of tree to either be retained or removed (Wagner et al, 2019) and perhaps their ecosystem services (Yang et al 2020).…”
Section: Knowledge Of Treesmentioning
confidence: 99%
“…Based on the Millennium Ecosystem Assessment (MEA) (Dorji et al 2019), the four categories of ecosystem services are cultural, provisioning, supporting/habitat, regulatory which are linked to community values, such as environmental conservation, wellbeing, socioeconomic, and spiritual sustenance provided by trees. In a study of tree and ecosystem services provided by trees in coffee plantations, Wagner et al (2019) observed that farmer perception is hinged on the prioritised ecosystem services and Yang et al (2020) underpinned the critical management of agroecosystems to the attitude of farmers to ecosystem services. However, the studies that led to these assertions were done with farmers having either a target crop (coffee agroecosystem) or temperate climate such as 800 mm annual rainfall in China.…”
Section: Introductionmentioning
confidence: 99%
“…In order to protect the ecosystems and enhance human well-being, the United Nations has articulated "Reduce inequality within and among countries" (SDGs10) and "Protect, restore and promote sustainable use of terrestrial ecosystems, sustainably manage forests, combat desertification, and halt and reverse land degradation and halt biodiversity loss" (SDGs15) as the Sustainable Development Goals (SDGs) [9]. Payments for ecosystem services (PES) provide a flexible approach to problem-solving that can transform uncompensated externalities into economic incentives that are important for protecting ecosystems, coordinating regional development, and achieving the SDGs [10][11][12][13]. PES has been scaled up globally to enable sustainable management of ecosystem services [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%